Modelagem e análise de uma turbina eólica offshore do tipo spar-buoy - Souza, Ricardo Nunes de (2019)
Driven by the constant increase in the demand for electric energy and the search for a clean and efficient energy matrix, the use of the potential of renewable energies, among them wind energy, has been increasing in the last decades. The wind industry is taking a new turn and starting exploration of offshore wind potential. Due to the great potential for wind power generation, the transition from onshore to offshore wind turbines has become a worldwide focus. Based on this, the present study is dedicated to the modeling and dynamic analysis of a coupled offshore system, consisting of a spar-buoy floating unit, a 5MW installed potential wind turbine and three catenary anchor lines in water depth of 320 meters. The fatigue study was performed only for the anchor lines considering eleven different unidirectional sea states. Dynamic modeling and analysis were performed through the SIMA-SESAM interface and the RIFLEX and SIMO softwares. The results obtained encompass different environmental conditions, and attest that the turbine, before the nominal wind speed, operates normally. The natural frequencies, important for the calibration of the model, were obtained by different methods.